Teknologi Elektroflokulasi Bertingkat Kombinasi Media Pasir - Arang Aktif sebagai Pengolahan Limbah Cair Industri Tapioka - Mulyono, Rifai Agung; Sapta, Wibowo Ady; Putri, Nawasari Indah (Poltekkes Kemenkes Tanjung Karang, 2022)
Tapioca industrial waste is still a problem and needs to be treated before being discharged into water bodies. The waste generated can be in the form of solid waste, gas waste, and liquid waste. This research is an experimental study and uses tapioca industrial wastewater samples which previously measured the parameters of TSS, BOD, COD, PH, and odor. Then processing is carried out by flowing continuously into the processor with multilevel electro flocculation technology, a combination of activated charcoal sand media with 12-volt electric current using control without activated charcoal sand media. The purpose of the study was to determine the electro flocculation ability of the combination of sand-activated charcoal media (thickness variations of 20cm, 40cm, 60cm, 80cm) in processing tapioca waste. The results showed a decrease in the levels of TSS, BOD, COD, pH, and odor. The most effective reduction was in the variation of activated charcoal sand media with a thickness of 60 cm. The results of the statistical test showed differences in the level of reduction in the pollutant content of tapioca waste TSS, BOD, COD, pH, and odor in the multistage electro flocculation process in the combination of sand–activated charcoal media with a p-value=0.00. The results of the study can be used as an alternative in the processing of tapioca industrial wastewater.